Institutional Financial Management Analysis in Manado State University (UNIMA) - Kawatu, Freddy Semuel; Tumiwa, Ramon Arthur Ferry; Mamuaya, Nova Christian; Rumagit, Merry Natalia (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2019)
The purpose of this study is to find out how are the financial management system and financial performance accountability at Manado State University (UNIMA). The research method uses a quantitative analysis approach, and data collection with open interview and interview techniques. The results of this study found that the level of suitability of the financial management system and the accountability of financial performance at UNIMA with the applicable theories and legislation (although there are still several factors that play a less optimal role include: a). Many financial management human resources are not in accordance with financial management expertise competencies, b). the accounting record system still combines manuals with computerization (only in the preparation of financial statements); c) unavailability of Financial Management Standards). Keywords: financial management, good governance, performance accountability